Seeing Is Believing: Do People Fail to Identify Fake Images on the Web? - Kasra, Mona; Shen, Cuihua; O’Brien, James (AoIR Selected Papers of Internet Research, 2016)
Images have historically been perceived as photographic proof of the depicted events. However, the growing ease with which digital images can be convincingly manipulated and then widely distributed on the Internet makes viewers increasingly susceptible to visual misinformation and deception. In situations where ill-intentioned individuals seek to deliberately mislead and influence viewers through forged online images, the harmful consequences could be substantial on both personal and social levels. In this paper, we describe an exploratory study of how individuals react, respond to, and evaluate the authenticity of images that accompany online stories in Internet-enabled communications channels (social networking site, blogs, email). Our preliminary findings suggest that people perform poorly at detecting skillful image manipulation, and that they often fail to question the authenticity of images even when primed regarding image forgery through discussion. We thus far found that viewers make credibility evaluation based mainly on non-image cues rather that the content depicted. Moreover, our study have revealed that in cases where context leads to suspicion, viewers apply post hoc analysis to support their suspicions regarding the authenticity of the image.